PRAKTIK SOSIAL PERTAMBANGAN: Suatu Studi Penanganan Konflik Oleh Sebuah Perusahaan Izin Clear and Clear di Ulayat Penghulu Nan Salapan, Nagari Lunang Utara - Alen Saprika; Afrizal Afrizal; Azwar Azwar (Universitas Andalas, 2019)
The concept of the clear and clean permit has been implemented since 2011 by the Indonesia government to produce sustainable mining practices. This concept is applied by the government due to the occurrence of conflicts in Indonesia. This article presents the results of research findings concerning the influence of clear and clean permits to social practices of mining. The study used structuration theory and using qualitative research method what has been studied is the use of government regulations by mining companies, related government agencies, and local communities to legitimize and understands their actions. A case PT. Tripabara operating in Nagari Lunang Utara has been studied. This article would like to show that although the company has obtained a clear and clean license, sustainable mining practices are not carried out. The article discussed the causes of unsustainable mining practices by PT. Tripabara. Two things will be revealed: the first is status of clear and clear permits obtained by the company is used by the company officials to claim that their mining practice is sustainable, while the community based their understanding of the company behavior on the company’s actions to tackle environmental problems and conflict of land acquisition.